Pelatihan Penggunaan Software Autocad Untuk Meningkatan Kompetensi Siswa-Siswi Smk Rigomasi Bontang - Ahmad Yani; Ratnawati Ratnawati; Masagus Moch. Yusuf (LPMP Imperium, 2020)
Tridharma Perguruan Tinggi is Education, Research, and Community Service. One of the obligations is to carry out Community Service, this is carried out in connection with the care of every institution or institution engaged in education. AutoCAD (Computer Aided Design) is a